Plasma Metabolite Profiles of Healthy Volunteers after Administration of a Thai Herbal Formula for Dizziness - Ranida Boonrak; Kajee Pilakasiri; Suksalin Boonranasubkajorn; Natchagorn Lumlerdkij; Pravit Akarasereenont (Traditional and Integrative Medicine)
The Thai herbal Yahom 20 formula (YHF20), is traditionally used for dizziness and fainting and off-label use for sleep aid, with inadequate substantial evidence afterward. This study’s primary objective is to employ metabolomics to investigate YHF20's effects, comparing it with lorazepam and a placebo in healthy volunteers. Phytochemical and metabolite profiling were performed using liquid chromatography-tandem mass spectrometry (LC-MS/MS) and LC/MS Q-ToF, respectively, on plasma samples from 90 healthy participants aged 20 to 60 years. These participants were randomized into three groups: YHF20 (n=30), Lorazepam (n=30), and Placebo (n=30). Principal Component Analysis (PCA) and Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA) were then conducted to identify differential metabolites and pathways. Six phytochemicals, including ellagic acid, glycyrrhizic acid, (E)-ferulic acid hexacosyl ester, 6-aldehydo-7-methoxy-isoophiopogonone B, melianol, and myristic acid were identified in YHF20. Despite PCA showing no significant overall metabolite profile differences among the groups, OPLS-DA pinpointed eight YHF20-associated metabolites, such as DHA ethyl ester, α-linolenic acid, (9Z)-9-octadecenamide, ricinoleic acid methyl ester, idazoxan, 13-HPODE, 12,13-DiHODE, and myristoleic acid, implying at anti-inflammatory pathway involvement, especially in α-linoleic and linoleic acid metabolism. No direct impact on sleep-related metabolites was found, the anti-inflammatory effects suggested by YHF20 could indirectly improve sleep quality by mitigating inflammation, a common sleep disruptor. These results highlight YHF20's potential for enhancing life quality through anti-inflammatory mechanisms. They offer a scientific basis for its traditional and anecdotal uses and suggest a novel approach to sleep quality improvement not previously documented.